Back Cover: Single‐Walled Metal–Organic Nanotube Built from a Simple Synthon (Chem. Eur. J. 11/2015). Issue 11 (9th March 2015) - Adarsh, Nayarassery N.; Dîrtu, Marinela M.; Naik, Anil D.; Léonard, Alexandre F.; Campagnol, Nicolo; Robeyns, Koen; Snauwaert, Johan; Fransaer, Jan; Su, Bao Lian; Garcia, Yann
<x xml:space="preserve">Abstract</x> Supramolecular self‐assembly of a trinuclear CuII secondary building unit, obtained from the reaction of CuSiF6 and a simple triazole‐carboxylate synthon in a green solvent, resulted in a single‐walled metal–organic nanotube. Interestingly, this material can be used for the entrapment of metallic mercury even after pressure relief; a property highly beneficial for mercury storage. For more details, see the Full Paper by Y. Garcia et al. on page 4300 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>